COVID-19 Lessons and Post-pandemic Recovery: A Case of Latvia - Šteinbuka, Inna; Austers, Aldis; Barānovs, Oļegs; Malnačs, Normunds (Frontiers in Public Health, 2022)
The decision of EU and the response of the national governments to COVID-19 crisis provide the basis for returning “back to normal”. A key challenge is the transition to economic recovery in the presence of the ongoing COVID-19 risk. Adequate policy mix and forward-looking actions of the public institutions are crucial to mitigate the devastating impact of the crisis and to preserve growth. Governments need to facilitate positive changes in the labor market, adjust the macroeconomic and fiscal regimes, and mitigate the post-crisis “fatigue” of societies. The turmoil of the EU economy is symmetrical, as the pandemic has affected all EU Member States, but the impact of the pandemic varies considerably from one country to another, as does their ability to absorb the economic crisis. Also, variation in the vaccination performance is partly due to different institutional characteristics across countries. Small countries are more vulnerable to external economic shocks; however, they can increase their resilience by efficient governance and social response. Extraordinary pandemic crisis can be seen as a stress test for the small and open Latvian economy, and it is worth analyzing the lessons that Latvia had learned and its future prospects. The aim of this paper is to evaluate the economic and social consequences of the ongoing crisis in Latvia, assess the effectiveness of the response of the government to the crisis, analyse people's perceptions, and to identify the future scenarios. The authors applied a special theoretical framework for the assessment of the effectiveness of institutions. Institutional analysis of crises response by the Latvian government reveals that the government managed to avoid serious functional disruptions; however, it failed to show convincing ability to learn by doing. The authors also provide a comprehensive analysis of the macroeconomic trends of the “COVID-sick” Latvian economy and conclude that future-oriented solutions relate to international competitiveness and that the key factor of competitiveness is a productivity renaissance. The pandemic crisis has fostered the state support for healthcare, which in Latvia for decades has been underfinanced. The right choice of fiscal instruments is crucial to accelerate the economic recovery and better healthcare. Research is based on the macroeconomic assessment and survey-based analysis. The comparison of statistically justified findings with the public perception helps formulate conclusions on the future scenarios and policies.